Social work students’ perception towards online learning during the COVID-19 pandemic - Lumanaj, Brilanda; Osmanaga, Fatbardha (Institute of Advanced Engineering and Science, 2024)
As a result of the pandemic, Universities in Albania faced this challenge for the first time during the COVID-19 pandemic. This transition created difficulties for both teachers and students. By studying students’ perceptions towards online learning, it is possible to identify their specific challenges and needs. It can provide a valuable perspective for improving the online learning experience in the future. The objective of this study is to examine the perceptions of social work students regarding the effectiveness and interaction experiences associated with their online learning during the COVID-19 pandemic at the University of Shkodra “Luigj Gurakuqi”, Albania, compared to classroom learning. This is descriptive research and includes quantitative and qualitative data. A structural questionnaire was distributed and followed by descriptive and thematic analysis. The sample included 84 students in a bachelor's program in social work. Students favored online courses for improving technical skills, dedicating more time to homework, and preferring email for queries. However, social interaction did not rise compared to classrooms. Students suggests blended learning for inclusivity, especially for those with financial, health, or job constraints. Ultimately, students preferred classroom learning for future teaching